Technological change and technical efficiency in the Malaysian mobile telecommunications industry - Mohamad, Noorihsan (2004)
This paper explores and analyzes the change in the productivity of Malaysian mobile telecommunications industry during the period 1996 to 2001. The data consists of a panel of five mobile service providers in Malaysia namely Celcom, DiGi, Maxis, TimeCel and TM Cellular. Productivity has been measured by the Malmquist index, using a Data Envelopment Analysis (DEA) technique. The Malmquist productivity measures are decomposed into two components:efficiency change and technical change index. The results showed that Total Factor Productivity (TFP) has increased significantly for the whole industry in which technical change has been the most important source of productivity growth to Malaysian mobile telecommunications industry. Low level of efficiency change in the industry indicates a great potential for the industry to increase productivity through higher utilization of technology as well as technological knowledge dispersion. Continuous training programs to familiarize and improve technical expertise appear to offer better prospects for Malaysian mobile telecommunications industry to achieve greater productivity growth.